RISE: sustainability: the three pillars / Norzawani Ibrahim and Mohd Hafeez Al-Amin Abdul Wahab - Ibrahim, Norzawani; Abdul Wahab, Mohd Hafeez Al-Amin (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Sustainability demonstrates that sustainability is a good idea for human behaviour by striking a balance between moral and economic ideals in our society. The three aspects of sustainability that are frequently taken into account are the economic, environmental, and social dimensions. Generally speaking, the majority of least developed nations (LDC) or underdeveloped countries (UDC) only pay attention to the economic aspect. Low-income nations known as least developed countries (LDCs) struggle with significant structural barriers to attaining sustainable development. They have little human capital and are quite susceptible to economic expansion. Meanwhile, developing nations aspire for excellence in both the economy and the environment. Most developing nations have started to address the environmental aspect while also experiencing economic growth.